2016
DOI: 10.1016/j.canlet.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

CD24 suppresses malignant phenotype by downregulation of SHH transcription through STAT1 inhibition in breast cancer cells

Abstract: Hedgehog (Hh) signaling has been found to be activated in breast cancer stem cells (BCSCs). However, the precise role of the BCSCs marker, CD24, remains unclear. Here, we describe a relationship between CD24 and Sonic Hedgehog (SHH), and reveal a role for this relationship in the induction of a malignant phenotype of breast cancer. CD24 siRNA-transfected breast cancer cells (BCCs) demonstrated higher expression of SHH and GLI1, increased anchorage-independent proliferation, and enhanced invasiveness and superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Western blotting was performed as described previously [28]. The protein-transferred membranes were incubated overnight at 4°C with primary antibodies for TrkB (1:200, sc-8316, Santa Cruz Biotechnology, Santa Cruz, CA, USA), p-TrkB (1:500, ab197072, Cambridge, MA, USA), BDNF (1:200, sc-546, Santa Cruz Biotechnology), MMP-2 (1:200, sc-10736, Santa Cruz Biotechnology), MMP-9 (1:200, sc-6840, Santa Cruz Biotechnology), E-cadherin (1:200, sc-7870, Santa Cruz Biotechnology), vimentin (1:200, sc-6260, Santa Cruz Biotechnology), SLUG (1:200, sc-15391, Santa Cruz Biotechnology), SNAIL (1:200, sc-10433, Santa Cruz Biotechnology), twist (1:200, sc-15393, Santa Cruz Biotechnology), VEGF-C (1:200, sc-7133, Santa Cruz Biotechnology), VEGF-D (1:200, sc-7603, Santa Cruz Biotechnology), p-MEK-1/2 (1:200, sc-7995, Santa Cruz Biotechnology), Erk1/2 (1:200, No9102 Cell signaling Technology), p-Akt1/2/3 (1:200, sc-101629, Santa Cruz Biotechnology), or Akt1/2/3 (1:200, sc-8312, Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting was performed as described previously [28]. The protein-transferred membranes were incubated overnight at 4°C with primary antibodies for TrkB (1:200, sc-8316, Santa Cruz Biotechnology, Santa Cruz, CA, USA), p-TrkB (1:500, ab197072, Cambridge, MA, USA), BDNF (1:200, sc-546, Santa Cruz Biotechnology), MMP-2 (1:200, sc-10736, Santa Cruz Biotechnology), MMP-9 (1:200, sc-6840, Santa Cruz Biotechnology), E-cadherin (1:200, sc-7870, Santa Cruz Biotechnology), vimentin (1:200, sc-6260, Santa Cruz Biotechnology), SLUG (1:200, sc-15391, Santa Cruz Biotechnology), SNAIL (1:200, sc-10433, Santa Cruz Biotechnology), twist (1:200, sc-15393, Santa Cruz Biotechnology), VEGF-C (1:200, sc-7133, Santa Cruz Biotechnology), VEGF-D (1:200, sc-7603, Santa Cruz Biotechnology), p-MEK-1/2 (1:200, sc-7995, Santa Cruz Biotechnology), Erk1/2 (1:200, No9102 Cell signaling Technology), p-Akt1/2/3 (1:200, sc-101629, Santa Cruz Biotechnology), or Akt1/2/3 (1:200, sc-8312, Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
“…Slides with xenograft tumors and GBC cells from patients were immunostained with primary antibodies for TrkB (1:100, sc-8316, Santa Cruz Biotechnology) and HIF-1α (1:100, sc-8711, Santa Cruz Biotechnology), followed by Alexa Fluor 488-labeled and Alexa Fluor 594-labeled secondary antibodies (1:1000, Invitrogen), as described previously [28]. …”
Section: Methodsmentioning
confidence: 99%
“…24 Moreover, development of the malignant phenotype was suppressed by CD + 24 via downregulation of SHH transcription through inhibiting STAT1. 25 The intratumoral and peritumoral CD4+ and CD8+ T cells are increased during the course of tumor regression under treatment of inhibition of the Hh signaling pathway. 26 Besides, in the immune system, differentiation of T cell, selection of T cell receptor, and activation of peripheral T cell are regulated by SHH.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mRNA level of STAT1 was significantly up-regulated in breast cancer, and increased in higher SBR grade, which predicted fast-growing, spreading tumors. A DNA microarray analysis identified that RNA interference of CD24, the breast cancer stem cells (BCSC) marker, could increase the expression of STAT1, which enhanced invasiveness and superior tumorigenicity [20]. Recently, Jeon et al .…”
Section: Discussionmentioning
confidence: 99%